Thermo-mechanical coupling behavior of needle-punched carbon/carbon composites - Han Meng; Zhang Xingyu; Wang Zhichao; Silberschmidt Vadim V.; Bi Qinsheng (Science and Engineering of Composite Materials)
Needle-punched carbon/carbon (NP C/C) composites are widely used in thermal protection systems for aerospace engineering. Oxidation and ablation affect their mechanical properties at high temperatures of service environment. A thermo-mechanical coupling model is proposed to predict the residual strength of oxidized bundles. A multiscale oxidation behavior of an NP C/C composite is simulated to investigate the progressive damage and oxidation of structures with thermo-mechanical coupling effects. Uniaxial tension experiments on the NP C/C composite were carried out at room temperature and 750°C to verify the proposed model. It is shown that mechanical properties of the composite decreased significantly after oxidation at 750°C-up to 40%, while the ultimate strain reduced by 5%. The proposed thermo-mechanical coupling model could be used to predict the failure and residual mechanical properties caused by the oxidation process.